Glocal Reflections of the Middle East Command (MEC) Project on the Regional Cold War. Issue 4 (4th July 2021) - Kasapsaraçoğlu, Murat
ABSTRACT: In the early 1950s, Western powers attempted to establish a regional alliance system with the participation of regional states to secure their interests. The Middle East Command (MEC) was the first project designed and imposed by the West. However, all actors in the region had different positions and policies towards such organizations. In this paper, the global and regional dynamics and developments affecting the creation of the MEC will be analysed from different perspectives using primary and secondary sources. The MEC project remained in the shadow of its successor, the well-known Baghdad Pact, and has received significantly less scholarly attention. By the same token, there is little literature on the MEC project and the existing literature is limited to the Western powers and Turkey. New studies reflecting the policies and positions of both global and regional actors are vital for the analysis of the Cold War in the Middle East. This paper mainly argues that global and local actors existed in two different worlds preventing their interests and priorities from overlapping. Therefore, under these circumstances, the MEC project and other alliances in the region failed and caused a tension shaping regional politics.